Field developmental plan analysis: a case study of ‘x’ reservoir - Taiwo Oludele Osunrinde; Iloka Chiamaka; Yawale Ahmad (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract Petroleum resources remain very important to the economic growth of several nations of the world even as oil price fluctuates in the current market today. The huge cost of exploration and exploitation of these resources makes it necessary for the attainment of high level of certainty in the methods adopted for its detection, quantification, planning and production. Mapping the right reservoir, understanding of reservoir characteristics most importantly; porosity, permeability, water saturation, thickness, and area extent of the reservoir, being able to reduce the uncertainties in these properties, making the right decision on when to inject water into the reservoir, where to locate these injectors and planning of where to drill new wells are very important factors that helps to determine the hydrocarbon reserves, cost of production and the degree of exploitation success rate and thus, needs to be treated with high level of certainty. This research work was, therefore, aimed at integrating several disciplines (Geologist, Reservoir Engineer, Well Engineer and Petroleum Economist) to carry out a detailed Field Development Plan (FDP) analysis for the reservoir in other to determine its success rate and economic viability. Simulations of three different cases of waterflood were analysed to decide the optimal development strategy to be applied to the field. Economic and sensitivity analyses were also carried out for all the cases suggested for the reservoir including the natural depletion case. Waterflood case 2 had NPV of $2,163,756,338 and the investment return of 47% and thus is recommended, since it is the best of all the cases.